Leishmaniasis in dogs from recycling centers and from a neighborhood with adjacent forest in an urban area of Londrina, Paraná, Brazil - Letícia da Costa; Eloiza Teles Caldart; Bruno Bergamo Ruffolo; Roberta dos Santos Toledo; Renata Cristina Ferreira Dias; Italmar Teodorico Navarro; Regina Mitsuka-Breganó; Odilon Vidotto; Roberta Lemos Freire (Semina: Ciências Agrárias, 2016)
The leishmaniasis are a group of globally widespread parasitic diseases caused by a protozoa of the genus Leishmania, the state of Paraná accounts for 98% of leishmaniasis human cases in southern Brazil and the dogs might serve as a sentinel of the risk of infection to humans in a given area. The aim of this work was to study the epidemiology of leishmaniasis in dogs residents in two different environments, they are: recycling of solid waste centers (Group 1) and a neighborhood adjacent to a forest (Group 2), both in Londrina, Paraná State, Brazil and to determine epidemiological variables associated to infection in these different realities. Serum samples, randomly collected, from 61 dogs from Group 1 and from 74 dogs from Group 2 were submitted to Indirect Immunofluorescence Antibody Test (IFAT) to research for anti-Leishmania IgG antibodies. Of the 135 dogs analyzed, 13 animals (9.6%) were positive; nine (14.7%) in Group 1 and four (5.4%) in Group 2, the difference between the groups is not statistically significant. These results suggest the presence of the protozoan Leishmania spp. in both environments studied which indicate potential for infection in the human population.